Sex differences in the winter activity of desert hedgehogs (Paraechinus aethiopicus) in a resource-rich habitat in Qatar - Pettet, C; Salazar, R; al-Hajri, A; al-Jabiri, H; Macdonald, D; Yamaguchi, N (Springer Nature, 2022)
Hedgehogs’ wide distribution and breadth of habitat use means they are a good model taxon for investigating behavioural responses to winter conditions, such as low temperatures and resource availability. We investigated the over-winter behaviour of desert hedgehogs (Paraechinus aethiopicus) in Qatar by radio-tracking 20 individuals and monitoring the body mass of 31 hedgehogs. Females spent more nights (38.63% of nights tracked) inactive than males (12.6%) and had lower monthly activity levels. The mean temperature on nights where hedgehogs were inactive was 14.9 °C compared with 17.0 °C when hedgehogs were active. By December, females lost a higher percentage of their November body mass than did males, but by February males had lost a higher percentage than females. We conclude that these sex differences in behaviour are a result of differing reproductive strategies with males becoming more active early in spring to search for mates, whereas female hedgehogs conserve energy for producing and raising young and avoid harassment by males. The winter activity of males may be facilitated by the resource-rich environment created by humans at this study site, and basking behaviour. This study highlights intraspecific and interspecific variation in behavioural strategies/tactics in response to winter conditions.